Towards an integrated development research approach - Zinsstag, Jakob; Pfeifer, Catherine; Ahorlu, C.; Hung Nguyen-Viet; Obrist, B. (2012)
In the past decade, development research within the Swiss National Centre of Competence in Research (NCCR) North-South gradually converged from disciplinary towards inter- and transdisciplinary approaches. Multiple examples from research on health, sanitation, and resilience highlight the benefits of closer cooperation, but also reveal the difficulties of connecting different epistemologies. Moreover, North–South research is faced with intercultural debates on its philosophical and ethical foundations. The ongoing globalisation of trade, transport, and communication does not allow for restriction to isolated local preferences but calls for exchange. Exchange, in turn, proves to be increasingly important in solving ever increasing problems of global change. Concepts developed within the NCCR North-South on social and reproductive resilience, integrated material flow, quantitative microbial risk and social science analyses, and health in social-ecological systems point towards integrated development research approaches. Such approaches have the power to bridge epistemological gaps between natural sciences and the humanities, connecting outcomes of research on natural resource management, health, sanitation, livelihoods, and governance. It is evident that the complexity of social development cannot be tackled using one single method. However, past experience with studies from different disciplinary perspectives in similar contexts points to the potential of mutual learning and understanding. The benchmark is less the theoretical foundation than empirical experience from within and outside the NCCR North-South, from which we can induce commonalities and methodological connections between scientific disciplines as well as between cultural paradigms. The aim of this session is to present different integrated development research approaches and to discuss them with the audience with a view to identifying gaps in mutual understanding, debating the validity of epistemological connections, and possibly moving towards integrated methods for development research.